2016
DOI: 10.1093/pm/pnw176
|View full text |Cite
|
Sign up to set email alerts
|

Isometric Back Exercise Has Different Effect on Pressure Pain Thresholds in Healthy Men and Women

Abstract: The results of this pilot study indicate that isometric back exercise produces local and remote hypoalgesia. Remote EIH was only demonstrated in women, supporting the influence of sex in the hypoalgesic response after exercise. The effect of isometric back exercise on pain sensitivity in patients with low back pain should be investigated in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
33
2
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 44 publications
8
33
2
3
Order By: Relevance
“…Aerobic and isometric exercise increased PPTs at local and remote assessment sites, which is in agreement with other studies showing a hypoalgesic response after exercise in healthy subjects [13][14][15][16]42] and patients with chronic pain [17,[43][44][45][46]. In contrast to these findings, earlier studies have demonstrated a lack of EIH response in patients with chronic pain [18,19,[47][48][49], and the results from a recent meta-analysis indicate that a subset of patients with chronic pain demonstrated impaired EIH responses compared with asymptomatic controls [11].…”
Section: Exercise-induced Hypoalgesiasupporting
confidence: 92%
See 1 more Smart Citation
“…Aerobic and isometric exercise increased PPTs at local and remote assessment sites, which is in agreement with other studies showing a hypoalgesic response after exercise in healthy subjects [13][14][15][16]42] and patients with chronic pain [17,[43][44][45][46]. In contrast to these findings, earlier studies have demonstrated a lack of EIH response in patients with chronic pain [18,19,[47][48][49], and the results from a recent meta-analysis indicate that a subset of patients with chronic pain demonstrated impaired EIH responses compared with asymptomatic controls [11].…”
Section: Exercise-induced Hypoalgesiasupporting
confidence: 92%
“…cycling or running) [13,14] and low-and high-intensity isometric exercise (i.e. muscle contraction without joint movement) [13,15,16]. In subjects with different musculoskeletal pain conditions, the effect of exercise on pain sensitivity is still controversial as both hypoalgesia [17,18] and hyperalgesia [19,20] have been reported.…”
Section: Resultsmentioning
confidence: 99%
“…Ademais, o estudo de Gajsar et al 9 demonstrou que as mulheres são mais sensíveis a estímulos isométricos. Isso torna interessante a prescrição do EI para esse grupo durante o treinamento, objetivando ganhos de força e hipertrofia, melhora nos aspectos hemodinâmicos e autonômicos, diminuindo valores da PAS em repouso e apresentando melhora na função e resistência vaso endotelial após estímulos crônicos em mulheres normotensas 11,12 .…”
Section: Discussionunclassified
“…Naugle et. al 8 verificaram que tanto o EI quanto o ED tem a particularidade de causar o efeito hipoalgésico causado pelo exercício, atenuando os limiares de dor, no entanto foi identificado que as mulheres respondem melhor ao protocolo isométrico e apresentam maior redução na dor muscular 9 . Além disso, tem sido demonstrado na literatura a usualidade do exercício isométrico, tanto em pacientes saudáveis como naqueles que possuem patologias cardiovasculares, auxilia na redução da pressão arte-rial e promove efeitos favoráveis na modulação da regulação autonômica, que combinado ao ED pode ser aconselhável para melhoras substanciais no sistema cardiovascular 10 .…”
Section: Introductionunclassified
“…Whilst there is debate regarding the exact pathway by which EIH operates it is consistently reported in healthy populations, and is thought to represent a normally functioning endogenous analgesic system [12]. The EIH response is reportedly influenced by factors such as gender [13,14] and activity levels [15,16]. Furthermore, studies in healthy individuals have demonstrated an EIH response at both local [17,18] and remote [18,19] assessment sites.…”
Section: Introductionmentioning
confidence: 99%